Diagnostic Performance of LI-RADS Version 2018 for Primary Liver Cancer in Patients With Liver Cirrhosis on Enhanced MRI - Liu, Xinai; Ni, Xiaoyan; Li, Yubo; Yang, Chun; Wang, Yi; Ma, Chunzheng; Zhou, Changwu; Lu, Xin (Frontiers in Oncology, 2022)
Purpose: To evaluate the diagnostic performance of the Liver Imaging Reporting and Data System (LI-RADS) version 2018 for differentiating hepatocellular carcinoma (HCC) from primary liver cancer (PLC) in patients with liver cirrhosis based on the updated 2019 WHO classification. Materials and Methods: From 2016 to 2021, 300 patients with surgically confirmed PLC and liver cirrhosis based on the updated 2019 WHO classification were eligible for this retrospective study (100 cases in each group: HCC, intrahepatic cholangiocarcinoma (ICC), and combined hepatocellular-cholangiocarcinoma (cHCC-CCA) groups). Two radiologists blinded to the final diagnosis independently assigned a LI-RADS category to each liver nodule. The diagnostic performances of the LR-5 category (definitely HCC) and the LR-M category (probably or definitely malignant, but not limited to HCC) were calculated for all nodules and small nodules (< 20 mm). Comparisons of categorical variables between groups were performed by one-way analysis of variance and the chi-squared or Fisher's exact test. Results: The mean age of the 300 patients (226 men and 74 women) was 57.40±11.05 years. The sensitivity and specificity of the LR-5 category for differentiating HCCs from other primary liver cancers were 81% (81 of 100) and 82% (164 of 200), respectively. The LR-M category had a sensitivity of 63% (126 of 200) for diagnosing non-HCCs (ICCs and cHCC-CCAs), with a specificity of 90% (90 of 100). The LR-5 category had a sensitivity of 75% (12 of 16) for diagnosing HCCs among small nodules (< 20 mm) with a specificity of 78.8% (26 of 33). In contrast, LR-M demonstrated a slightly higher specificity (93.8%) and sensitivity (73.8%) for diagnosing non-HCCs with a tumor size<20 mm. Conclusion: The LR-5 category as well as the LR-M category of LI-RADS version 2018 can effectively distinguish HCC from other primary hepatic malignancies in patients with liver cirrhosis, especially those with small nodules (< 20 mm).